Field-induced self-assembly: does size matter? - Robinson, D; Wilson, M (Taylor and Francis, 2018)
Simulated external electric fields are applied to polarisable species containing either a monodisperse of bidisperse distribution of polarisabilities. The magnitude of the external field and the polarisabilities are systematically varied. The application of an external field (of sufficient magnitude) is found to induce chain formation (as expected). The monodisperse systems are found to ‘self-assemble’ with larger induced dipole moments effectively clustering in chains as a result of significant dipole-induced dipole effects. The distribution of the chain lengths is characterised as a function of the applied field and the atom polarisability. For the bidisperse systems, the external field induces chain formation and a partial segregation, in which the more polarisable species preferentially form chains. The chain lengths are again determined as a function of field strength and the atom polarisabilities. Scaling behaviour is analysed.